Time Saver or Time Sapper? An Examination of Body-Worn Camera Impact on Case Disposition Timelines - Pimley, Nicholas (Criminal justice review, 2024)
In the last few years, a considerable volume of body-worn camera (BWC) studies has evaluated to what extent this technology influences a range of policing outcomes. However, to date, a limited body of research explores how the implementation of this technology influences court-based outcomes. Using interrupted series analysis, and a sample of 13,000 incidents from a small police department, this research evaluates to what extent the implementation of BWCs impacted the adjudication process through an analysis of time to disposition, rate of convictions, and rate of dismissals. The results of our study show partial support for claims being made about the impact of BWCs on the court system. Namely, the number of incidents being referred for prosecution and the number of guilty decisions being reached saw a marginal increase after the implementation of BWCs. Additionally, the number of days to complete adjudication saw a decrease overall during the post-implementation period. The policy implications of these findings are discussed.